2021
DOI: 10.1002/prp2.704
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of STAT3 by BP‐1‐102 inhibits intracranial aneurysm formation and rupture in mice through modulating inflammatory response

Abstract: As an inhibitor of STAT3, BP‐1‐102 can regulate the inflammation response caused by vascular smooth muscle cells (VSMCs) by inhibiting the JAK/STAT3/NF‐κB pathway, thereby attenuating the symptoms of intracranial aneurysm (IA). IA mouse model was established by stereotactic injection of elastase to evaluate the effect of BP‐1‐102. The expression levels of smooth muscle markers and matrix metalloproteinases (MMPs) were detected by qRT‐PCR, and the levels of inflammatory factors were detected by ELISA and qRT‐PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
(89 reference statements)
0
11
0
Order By: Relevance
“…In addition to that, polymorphism in the genotype of the NF-κB promoter was linked to a lower risk of IAs [ 17 ]. Similar to clinical studies, experimental studies using different animal models showed the elevated mRNA expression, protein levels, and/or activation of NF-κB in IA tissue compared to normal control arteries ( Table 2 ) [ 8 , 20 , 23 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 40 , 43 ]. The animal experimental studies revealed that blocking NF-κB P50 expression and NF-κB activation reduced the incidence of IA formation ( Table 3 ) [ 8 , 40 ], while enhanced NF-κB activation was linked to increased IA formation ( Table 3 ) [ 11 ].…”
Section: Discussionmentioning
confidence: 62%
“…In addition to that, polymorphism in the genotype of the NF-κB promoter was linked to a lower risk of IAs [ 17 ]. Similar to clinical studies, experimental studies using different animal models showed the elevated mRNA expression, protein levels, and/or activation of NF-κB in IA tissue compared to normal control arteries ( Table 2 ) [ 8 , 20 , 23 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 40 , 43 ]. The animal experimental studies revealed that blocking NF-κB P50 expression and NF-κB activation reduced the incidence of IA formation ( Table 3 ) [ 8 , 40 ], while enhanced NF-κB activation was linked to increased IA formation ( Table 3 ) [ 11 ].…”
Section: Discussionmentioning
confidence: 62%
“…The mortality rate of IA-induced SAH is 50% worldwide. The living quality of only 30%-45% survivors returns to their pre-onset state [ 4 ]. History of hypertension, genetics, sex, age, and cigarette smoking are potential contributors of aneurysm rupture [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhixian Jiang et al . demonstrated that BP-1-102 suppressed the JAK/STAT3/NF-κB pathway in intracranial aneurysms, reduced the vascular inflammatory response, alleviated the symptoms of intracranial aneurysms and prevented their rupture ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Qi-Ying Wu et al demonstrated that BP-1-102 inhibited JAK2/STAT3/NF-κB pathway activation in a mouse abdominal aortic aneurysm model, thereby reducing the expression of proinflammatory cytokines, decreasing inflammatory cell infiltration, and ultimately impeding the development and progression of abdominal aortic aneurysms (38). Zhixian Jiang et al demonstrated that BP-1-102 suppressed the JAK/STAT3/NF-κB pathway in intracranial aneurysms, reduced the vascular inflammatory response, alleviated the symptoms of intracranial aneurysms and prevented their rupture (39,40).…”
Section: Discussionmentioning
confidence: 99%